Afterword: Memory worlds in times of Corona. (October 2020) - Erll, Astrid
This afterword addresses the complex temporal and global dynamics of the coronavirus pandemic. After considering some of the new social rhythms that have emerged in the wake of Covid-19 around the world, it turns to the role of collective memory before, during and after corona. The aim is to provide a basic grid for how the Covid-19 pandemic could be addressed using memory studies expertise and concepts such as premediation, memorability, memory (ab)use, national memory, colonial memory, racial stereotypes, the digital archive, generational memory, or Anthropocene time.